Aspek Hukum Janji Prakontrak Dalam Pranata Hukum Kontrak Indonesia - Asnawi, Natsir (UI Scholars Hub, 2019)
The precontractual issues in Indonesia had been raised due to the existing gap between the codification of contract law and the practical needs in contract law. As an umbrella act of civil law, The Indonesian Civil Code (Burgerlijke Wetboek) has yet regulate precontractual issue. Likewise, the judicial practice remains to establish law certainty (formalitiy of a contract), instead of giving justice to the parties who get injured on account of breaking the precontractual promises. Due to effort of updating the contract law, its substance should attach precontractual as a crucial term. Precontractual promissory should be stated as legally bound to the parties. Hence, act of lawlessness toward precontractual promise is about to punished by either of these legal instrument: 1) tort (onrechtmatige daad), by condemning the violator to redeem the other party’s interest (reliance interest); 2) breach of contract, by condemning the violator to redeem, not merely toward reliance interest, but also toward expectation interest of injured party; or 3) consumer protection, by condemning the violator either redeem some reliance interest or to continue or not of performing a specific act which had been declared in precontractual phase.